Great Expectations and the End of the Depression - Eggertsson, Gauti B (American Economic Review, 2008)
This paper suggests that the US recovery from the Great Depression was driven by a shift in expectations. This shift was caused by President Franklin Delano Roosevelt's policy actions. On the monetary policy side, Roosevelt abolished the gold standard and—even more importantly—announced the explicit objective of inflating the price level to pre-Depression levels. On the fiscal policy side, Roosevelt expanded real and deficit spending, which made his policy objective credible. These actions violated prevailing policy dogmas and initiated a policy regime change as in Sargent (1983) and Temin and Wigmore (1990). The economic consequences of Roosevelt are evaluated in a dynamic stochastic general equilibrium model with nominal frictions. (JEL D84, E52, E62, N12, N42)